Analysis of cognitive development of tahfiz children of the Qur'an in the 21 st century (case studies in the SD Muhammadiyah Pajangan 2 Berbah) - Putri Wahyuningsih; Himmatul Hasanah; Ahmad Tarmizi Hasibuan (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This paper examines the analysis of the development of aspects of the (cognitive) knowledge of children in Muhammadiyah 2 Berbah Elementary School, especially children who attend the Tahfidz Al-Quran program at the elementary school. After the research was conducted it was found that students who followed the Tahfidz Al-Quran program experienced an increase in their cognitive development. The more children memorize the Koran the more the level of cognitive development develops. This is also a proof for parents of students, if participating in the tahfidz program the Koran is open to burden on students and makes their learning outcomes decline, but with the Tahfidz Al-Quran program makes students' cognitive development better.In general, this paper presents 5 (three) questions. First, what is meant by knowledge / cognitive? Second, what is meant by the development of students? Third, what are the cognitive levels? Fourth, what are the developmental aspects of students? And finally is how is the relationship between students who follow Tahfidz Al-Quran with the cognitive development of students?This study is expected to be able to add scientific treasure and become a reference in studying children's cognitive development and its relationship with the Tahfidz Al-Quran program.Keywords: Cognitive, Learners